Sexual and Reproductive Health Implications of the Cultural Practice of “Rites Of Passage” Among Adolescent Females: The Case of Dipo in Ghana: Relevance of Cultural Rites of Passage (Dipo) (Journal of Science and Technology, 2025)
Objective: The study explored the relevance and implications of Dipo (a puberty rite of passage in Ghana) on the sexual and reproductive health and rights of adolescent females in the Krobo culture.Design/Methods: Using a qualitative research design, a total of 23 participants were recruited using a purposive sampling method for the study. Data were gathered through in-depth interviews, focus group discussions, and analysed using the Attride-Stirling thematic network analysis.Results: Findings indicated that the Dipo represents a cultural means of instruction aimed at encouraging chastity and marriage for adolescent females. Also, the sexual and reproductive health education aimed towards female adolescents during Dipo was found to contain over-generalised, inaccurate, and fear-inducing messages. Within the Dipo rite of passage, limitedopen communication about sexual health and sexual intercourse was reported. Instead, information was unidirectional and postponed to later ages for adolescent females. As a consequence, adolescent females may experience delayed development in their identities as a ‘Krobo’ woman, and also have limited information on safe sex practices in modern times.Conclusion: The Dipo rite of passage is increasingly viewed as having diminishing relevance and potentially negative consequences for the sexual and reproductive health of adolescent females, partly due to the lack of explicit, age-appropriate sexual health education. In light of modern social changes and the growing recognition of the importance of safe sex practices, this study underscores the need to integrate explicit sexual education into traditional rites. This integration would enhance the relevance of such practices and help protect adolescent health within evolving socio-cultural contexts.